(untitled) (Journal of the College of Basic Education, 2022)
Terrorism in all its forms is a dangerous scourge that threatens humanity in all its organisations, institutions and groupsTerrorism and what it entails in its essence of fanaticism, isolation and extremism spread like a malignant tumor to pay offhuman beings to annihilate every aesthetic value in life in order to achieve evil selfish goals withoutControls stem from normal instinct and the human dignity related to it. Terrorism was not born in this era, as we find it. In all the stages of human history stunt stages onEarth, whether before or after the emergence of monotheistic religions, and it emerged in its ugliest form in the twentieth centuryFor its central intersection with civilization and civil. the international legal, economic and political system; FatalIndividuals: Institutions and States: Until most of the countries of the world became burdened with carrying it and striving hard forget rid of it.